Pregnancy with Maternal Caroli’s Disease - Case Report - Meenakshi, T Sahu; Chitranshu, Vashishtha; Anuradha,; Shruti, (Journal of Women's Reproductive Health, 2015)
A maternal case of Caroli’s disease in pregnancy is described, with attention to diagnostic imaging, obstetric management, and maternal–fetal risks.